Predictors of physical activity for weekdays and weekends among adolescent – a cross-sectional study in Sarawak, Malaysia - Cheah, W.L; Helmy, Hazmi; Chang, C.T (Gdansk University of Physical Education and Sport, Poland, 2015)
This study aimed to describe the patterns of physical activities both at weekends and on weekdays and to identify their associated factors. Material/Methods This was a cross-sectional study conducted among secondary school students aged 13-15 years old in Kuching Division, Sarawak, Malaysia. A self-administered questionnaire was used to collect socio-demographic information and to measure perceived barriers, self-efficacies and social influences. Anthropometric measurements were taken and used to determine BMI-for-age, while pedometers were used to assess the physical activity levels. Data were analyzed using SPSS. Results A total of 474 students from six secondary schools participated. About 16% of the respondents were overweight and obese, majority of them males. The mean BMI was 21.21±12.93, higher among males. The mean steps per day were 6251.37±3085.31, with weekends recorded a higher number of steps. The number of steps among males was higher than among females. On weekdays, self-motivation scores significantly predicted the participants’number of steps/physical activity rate (b = 521.43, 95% CI -72.78 to 1050.19). At weekends, lack of interest and knowledge scores (b = -427.82, 95% CI -837.72 to 17.92) and making choices scores (b = 737.41, 95% CI -197.94 to 1276.88) were significant to predict the number of steps/physical activity levels. Conclusions These findings indicated the importance of investigating predictors of physical activity for weekdays and weekends. Thus, efforts should focus on how to motivate adolescents to be more physically active targeting the identified predictors for weekdays and week ends.